Determination of the Age and Growth of Glossogobius Giuris (Hamilton-Buchanan, 1822) Using Sectioned Otolith (Bangladesh Journal of Zoology, 2012)
The freshwater gobi, Glossogobius giuris (Hamilton-Buchanan, 1822)  (Gobiidae: Perciformes) is an important freshwater fish species in Bangladesh. The  age and growth of this species, collected from the river Titas, Brahmanbaria, were  studied with transverse sections of otoliths. The otoliths opaque zones that are  formed every year were the annual rings. The growth of this species was rapid  during the first two years, reaching 18.5 cm in total length. Most of the specimens  were 1-2 years old and accounted for 90% in total. The maximum age recorded  was five years with 19.5 cm in total length. The von Bertalanffy growth parameters  L? and K for this species were 19.58 cm and 1.36/year, respectively. The study  indicated that the age and growth of G. giuris can be determined using its  sectioned otolith. DOI: http://dx.doi.org/10.3329/bjz.v40i1.12889 Bangladesh J. Zool. 40(1): 13-19, 2012